2019
DOI: 10.1177/0144598719867478
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of coal-measure source rock and gas accumulation belts in marine-continental transitional facies fault basins: A case study of the Oligocene deposits in the Qiongdongnan Basin located in the northern region of the South China Sea

Abstract: This study carried out the development and distribution prediction research on coal-formed gas accumulation belts from the perspectives of the development and distribution of the coal measure source rock and the thermal evolution degrees of those rock masses in marine-continental transitional facies fault basins. The purpose of the current study was to improve the accuracy of gas reservoir explorations in the sea areas. The methods used in this study were based on the systematic analyses of the drilling, loggi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The vitrinite reflectance of the Pinghu coals (0.55-1.28%) is also much higher than the Laisong coal, owing to deeper depth of burial and steeper geothermal gradient in the Xihu Sag (Liu et al, 2020) (Kang et al, 2020). The coal measure of the Oligocene Yacheng Formation is the most important source rock sequence in the Qiongdongnan Basin in the South China Sea region that had entered a phase of mass gas generation, owing to its high degree of thermal evolution and subsidence (Gongcheng et al, 2019).…”
Section: Comparisons With Regional Depositsmentioning
confidence: 99%
“…The vitrinite reflectance of the Pinghu coals (0.55-1.28%) is also much higher than the Laisong coal, owing to deeper depth of burial and steeper geothermal gradient in the Xihu Sag (Liu et al, 2020) (Kang et al, 2020). The coal measure of the Oligocene Yacheng Formation is the most important source rock sequence in the Qiongdongnan Basin in the South China Sea region that had entered a phase of mass gas generation, owing to its high degree of thermal evolution and subsidence (Gongcheng et al, 2019).…”
Section: Comparisons With Regional Depositsmentioning
confidence: 99%
“…Coal measure source rock is an important part of gas yield and petroliferous source rock; it can be formed in various types of basins, and it is widely developed around the world. The mechanism and distribution laws governing coal measure source rock formation have been the subject of extensive inquiry [1][2][3][4][5][6][7][8]. Coal measure source rock has been used as a potential source rock for many years; M Lutz found that coal measure source rock from the Carboniferous could be a source for the large-scale generation of methane, and the same gas pool has been found in northwest Europe's southern Permian coal measure source rock [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…According to the research, coal measure source rock could even have a special type of "self-generation and self-storage" capacity according to a geochemical characteristic comparison [11][12][13][14]. With the help of further research, coal-formed gas has increasingly been found in various basins [7,15,16] and by researchers who are simultaneously working on the factors that limit the petroleum potential of coal measure source rock [5,[17][18][19][20]. However, coal seams are not only warm beds of gas but also a source of oil.…”
Section: Introductionmentioning
confidence: 99%